Incidence of and risk factors for bile duct stones after living donor liver transplantation: An analysis of 100 patients. Issue 9 (15th December 2014) - Senoo, Takemasa; Ichikawa, Tatsuki; Taura, Naota; Miyaaki, Hisamitsu; Miuma, Satoshi; Shibata, Hidetaka; Honda, Takuya; Takatsuki, Mitsuhisa; Hidaka, Masaaki; Soyama, Akihiko; Eguchi, Susumu; Nakao, Kazuhiko
<x xml:space="preserve">Abstract</x> Aim Although bile duct stone (BDS) is one of the biliary complications of liver transplantation, analytical studies, particularly on living donor liver transplantation (LDLT) cases, are rare. This study aimed to clarify the incidence of and risk factors for BDS following LDLT. Methods We retrospectively reviewed the medical records of 100 patients who underwent LDLT at our institute from August 2000 to May 2012, and analyzed their clinical characteristics and risk factors for BDS. Results Of these, 10 patients (10.0%) developed BDS during the observation period. The median follow‐up period to BDS diagnosis was 45.5 months (range, 5–84) after LDLT. Univariate analysis revealed male sex, right lobe graft and bile duct strictures as factors that significantly correlated with BDS formation. Multivariate analysis revealed bile duct strictures (odds ratio, 7.17; P = 0.011) and right lobe graft (odds ratio, 10.20; P = 0.040) to be independent risk factors for BDS formation. One patient with BDS and biliary strictures succumbed to sepsis from cholangitis. Conclusion In the present study, right lobe graft and bile duct strictures are independent risk factors for BDS formation after LDLT. More careful observation and monitoring are required in the patients with high‐risk factors.